2016
DOI: 10.1111/ger.12235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral health‐related conditions that could trigger accidents for patients with moderate‐to‐severe dementia

Abstract: Hospitalised moderate-severe dementia patients had a high prevalence of oral health conditions unnoticed by doctors and ward staff that may increase risk of incidents and/or accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…The third point of our intervention was oral health and hygiene (OH). Patients with dementia, especially in advanced phases, often have poor oral health and OH and missing teeth [44,45]. Ortega et al described the oral health of older patients with and without OD according to the OHI-S and found that both groups had poor OH but that it was significantly worst in OD patients and a higher risk of AP [46].…”
Section: Discussionmentioning
confidence: 99%
“…The third point of our intervention was oral health and hygiene (OH). Patients with dementia, especially in advanced phases, often have poor oral health and OH and missing teeth [44,45]. Ortega et al described the oral health of older patients with and without OD according to the OHI-S and found that both groups had poor OH but that it was significantly worst in OD patients and a higher risk of AP [46].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the general health in the human body gives rise to the appropriate oral and dental health ( 10 , 11 ). Tooth decay and periodontal complications are considered as the most well-known diseases ( 12 14 ). The instability of daily patterns and changing lifestyles have caused these diseases to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Oral factors, such as periodontal disease, reduced number of remaining teeth, and systemic bacterial infection spreading from the oral cavity, have recently been reported to increase the risk of dementing disorders123. The sensitivity for the detection of asymptomatic cerebral microbleeds (CMBs), which are an early stage of cerebral hemorrhage45 has been enhanced by susceptibility-weighted imaging (SWI), a new MRI brain imaging technique.…”
mentioning
confidence: 99%